Transgenerational effects of maternal and grandmaternal age on offspring viability and performance in Drosophila melanogaster. (July 2017) - Bloch Qazi, Margaret C.; Miller, Paige B.; Poeschel, Penny M.; Phan, Mai H.; Thayer, Joseph L.; Medrano, Christian L.
Graphical abstract: Abstract: In non-social insects, fitness is determined by relative lifetime fertility. Fertility generally declines with age as a part of senescence. For females, senescence has profound effects on fitness by decreasing viability and fertility as well as those of her offspring. However, important aspects of these maternal effects, including the cause(s) of reduced offspring performance and carry-over effects of maternal age, are poorly understood. Drosophila melanogaster is a useful system for examining potential transgenerational effects of increasing maternal age, because of their use as a model system for studying the physiology and genetic architecture of both reproduction and senescence. To test the hypothesis that female senescence has transgenerational effects on offspring viability and development, we measured the effects of maternal age on offspring survival over two generations and under two larval densities in two laboratory strains of flies (Oregon-R and Canton-S). Transgenerational effects of maternal age influence embryonic viability and embryonic to adult viability in both strains. However, the generation causing the effects, and the magnitude and direction of those effects differed by genotype. The effects of maternal age on embryonic to adult viability when larvae are stressed was also genotype-specific. Maternal effects involve provisioning: older females produced smaller eggs and larger offspring. These results show that maternal age has profound, complex, and multigenerational consequences on several components of offspring fitness and traits. This study contributes to a body of work demonstrating that female age is an important condition affecting phenotypic variation and viability across multiple generations.